Snaq: A Dynamic Snakemake Pipeline for Microbiome Data Analysis With QIIME2 - Mohsen, Attayeb; Chen, Yi-An; Allendes Osorio, Rodolfo S.; Higuchi, Chihiro; Mizuguchi, Kenji (Frontiers in Bioinformatics, 2022)
Optimizing and automating a protocol for 16S microbiome data analysis with QIIME2 is a challenging task. It involves a multi-step process, and multiple parameters and options that need to be tested and determined. In this article, we describe Snaq, a snakemake pipeline that helps automate and optimize 16S data analysis using QIIME2. Snaq offers an informative file naming system and automatically performs the analysis of a data set by downloading and installing the required databases and classifiers, all through a single command-line instruction. It works natively on Linux and Mac and on Windows through the use of containers, and is potentially extendable by adding new rules. This pipeline will substantially reduce the efforts in sending commands and prevent the confusion caused by the accumulation of analysis results due to testing multiple parameters.